ADDITION OF FLOW TRANSMITTER AS A CONTROL TO ENHANCE THE ACCURACY OF OIL PRODUCTION READINGS - Huda, Miftakhul (Universitas Islam Balitar Blitar, 2025)
This research aims to evaluate the effectiveness of adding a flow transmitter as a control in improving the accuracy of readings of petroleum production results, which previously used transmitter levels as a control. The use of transmitter levels as a control has been shown to affect watercut analyzer readings, resulting in lower and less accurate flow counts. In this research, a comparative analysis was carried out between the control system that uses a level transmitter and the control system that uses a flow transmitter. The methods used include field data collection, statistical analysis, and performance evaluation of the two systems. The results showed that the use of a flow transmitter as a control could increase the accuracy of flow readings by about 13.2% compared to the previous control. This improvement not only improves the accuracy of flow measurements, but also has a positive impact on operational efficiency and management of petroleum resources. This research is expected to contribute to the petroleum industry in an effort to improve a more effective and efficient production measurement and control system.